436 PRONE THORACOSCOPIC ESOPHAGECTOMY FOR PATIENTS WITH LOW PULMONARY FUNCTION. (17th September 2021) - Takiguchi, Gosuke; Oshikiri, Taro; Horikawa, Manabu; Kitamura, Yu; Horie, Kazumasa; Urakawa, Naoki; Hasegawa, Hiroshi; Yamamoto, Masashi; Shingo, Kanaji; Matsuda, Yoshiko; Yamashita, Kimihiro; Matsuda, Takeru; et al.
Abstract:  : Thoracoscopic esophagectomy in the prone position (TEP) for esophageal cancer is reported to have superiority in preserving postoperative respiratory function and reducing postoperative respiratory complications. In Japan, the majority of patients with esophageal cancer are smokers and have obstructive ventilation disorders. But, the feasibirity and safety of TEP for patients with low respiratory function is unclear. Objectives: To clarify the feasibirity and safety of TEP for esophageal cancer patients with obstructive respiratory function. Methods: The 95 patients with obstructive respiratory disorder who underwent TEP and gastric tube reconstruction via posterior mediastinal route for esophageal cancer from January 2016 to April 2019 were divided into the two groups, low respiratory function (LRF) group and the control group. Short-term outcomes were compared between two groups. Results: The control group was 73 cases, and the LRF group was 22 cases. Propensity score matching using age, gender, cT, and cN as covariates was used to identify matched patients (22 per group) in both groups. There were no differences in operation time of overall and intrathoracic part, or blood loss in each group. In the postoperative complications, pneumonia (13.6% vs. 9.1%), recurrent laryngeal palsy (18.2% vs. 22.7%), anastomotic leakage (13.6% vs. 13.6%) and hospital stay (36.3 days vs 27.5 days) were no differences in both groups. Conclusion: TEP can be feasible and safe for the patients with obstructive ventilation disorder and low respiratory function.